Obstacles of Biology Student Teachers during the Course of Biology Learning Strategies and Its Solution - SUGIHARTO, BOWO; COREBIMA, ALOYSIUS DURAN; SUSILO, HERAWATI; IBROHIM, IBROHIM (Bioedukasi: Jurnal Pendidikan Biologi, 2016)
Biology Learning Strategy (BLS) is an important course that constitutes the competence of biology student teachers, especially pedagogy competence. This study aims to describe the learning strategy of the biology teacher candidates, problems they encountered, and the chosen learning solution in BLS course. This explorative survey was conducted in March-April 2016. The study involved 176 participants. The participants were students of 4th semester biology student teachers who took BLS course. The data were collected by using a semi-open and open questionnaire. The analysis of the data was qualitative data analysis model of Miles and Huberman which includes data reduction, data presentation, and drawing conclusions and verification. The study concludes that the percentage of the way the students learned BLS by understanding is 53.4%, memorizing and understanding is 36.9%, memorizing only is 5.7%, and the other is 7%. Problems experienced by the students in learning BLS include discomfort during a rowdy class, lack of ability to understand, lack of confidence to perform, lack of ability to choose a strategy or apply the materials in the practice, as well as the difficulty to memorize. The way to overcome the problems in learning BLS is quite various and it can be classified into four categories namely changing learning strategies, increasing the intensity of learning, improving motivation, and increasing the frequency of exercise.